LOCAL CULTURE REPRESENTATION IN INDONESIA COMICS - Pradnyanita, A.A. Sagung Intan; Yudha, A.A. Ngurah Bagus Kesuma; Lestari, Ni Putu Emilika Budi (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Comics are one of the entertainment media that is easily found in everyday life. Through comics, readers can recognize visuals or understand the storyline that is presented easily. Comics are usually presented in book form, but in the current development comics can be enjoyed online through smartphone media. Through comics, people can get to know culture or even create culture. Without realizing it, comics invade the conscious realm indirectly, thus facilitating the entry of foreign cultures. Comics have an influence on culture and culture and can be integrated in comics. In Indonesia, comics become a popular reading. Indonesian comics are cultural results. The beginning of the existence of Indonesian comics was heavily influenced by the West and China, then replaced by a period of national personality. Currently many Indonesian comic artists introduce Indonesian culture through comics, including Tantraz, Garudayana, Mantradeva, Warrior God, and many more. In this article, we will review more about how comics correlate and represent culture in Indonesia both through themes, characterizations, and the storyline presented.